Demanda total de la Carga Eléctrica de la Edificación de la Universidad Técnica de Cotopaxi, La Maná" - Albarrasín Reinoso, David Fernando (2014)
The research involves the study of electricity demand, making the analysis of many parameters, at the end, there must be a clear view of the conditions from the drivers to the potential demand, technical analysis and design of the best conditions which includes determining the voltage of each electrical components used in the building of higher education taking into account organizational and legal aspects concerning the installation. With the first draft the necessary information to determine where the highest electrical demand of the building of the Cotopaxi Technical University La Mana was collected, and to know the status of drivers and an analysis of the maximum demand obtained and the utilization of existing electrical equipment in the building. For the study of electricity demand is important the classification of consumers. In the building, must be done the study of peak demand as an industrial customer , for these customers will be held according to factors such as division and land use, characteristics of the infrastructure and will be established as a result of a founded analysis of the values of unit demand to be considered in the design . The benefit that leaves us the study of demand is that the value of the total electric charge is obtained and based on these results we determined sizing breaker and cable and conductor gauge or ducts. Finally, we determined where the higher power consumption which occurs in the area of computer labs with an existing 40 KVA load across the whole University.